Neutral angle and forward slip during high-speed rolling in finishing blocks of wire mill stands - A. A. Gorbanev; V. V. Fillippov; S. M. Zhuchkov; V. A. Tischenko; A. B. Steblov; A. D. Shevchenko (Литьë и металлургия, 2001)
On the basis of investigation results analysis it's been^ established that influence of mass forces on the moment arm coefficient with rolling speed of up to 150 m/s at exit from the block must be taken into account in the last two or three block stands; joint influence of interst and efforts and mass forces on the coefficient of moment arm mostly affects odd block stands, which must be considered while calculating power rolling parameters.